2022
DOI: 10.3389/fpsyt.2022.813103
|View full text |Cite
|
Sign up to set email alerts
|

The Multivariate Effect of Ketamine on PTSD: Systematic Review and Meta-Analysis

Abstract: BackgroundPost-traumatic stress disorder (PTSD) is a serious stress-related disorder caused by traumatic experiences. However, identifying a key therapy that can be used for PTSD treatment remains difficult. Ketamine, a well-known dissociative anesthetic, is considered safe to be used in anesthesia, pain management, and antidepressant actions since 1970. At present, it is still controversial whether PTSD can be treated with ketamine. The authors performed a meta-analysis to determine whether the use of periope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(55 citation statements)
references
References 57 publications
1
53
0
1
Order By: Relevance
“…Our study supports Du et al's results [33] and builds on the importance of including psychotherapy with pharmacological treatment for PTSD. Psychotherapy is a rst-line treatment for PTSD, though its effects are short-lived.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our study supports Du et al's results [33] and builds on the importance of including psychotherapy with pharmacological treatment for PTSD. Psychotherapy is a rst-line treatment for PTSD, though its effects are short-lived.…”
Section: Discussionsupporting
confidence: 91%
“…A paired-samples t test showed a signi cant decrease (p = 0.003) in PCL-5 scores (pre-treatment mean 55. 33, SD = 11.52 to post-treatment mean 27.11, SD = 12.36) 95% CI (13.11, 43.33), Cohen's d = 1.44.…”
Section: Cohort E Cacy Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Далі з'явилися дані про ефективність кетамінової терапії при тривожних розладах [156], обсесивно-компульсивному розладі [6,99], ПТСР [40], розладах харчової поведінки, залежностях від вживання психоактивних речовин [99] та хронічних больових синдромах [15].…”
Section: кетамінunclassified
“…Ketamine also has a moderate effect treating agitation and aggression associated with PTSD (Liriano et al, 2019; Tran & Mierzwinski-Urban, 2019). However, conflicting reports have shown that ketamine is not effective in ameliorating PTSD-like symptoms in soldiers on the battlefield and, in some cases, can even exacerbate them (Du et al, 2022; McGhee et al, 2014; Mion et al, 2017; Schönenberg et al, 2008).…”
mentioning
confidence: 99%